THE ROLE OF HIGHER SCHOOL IN NATIONAL ECONOMY STRENGTHENING - Lidia I. Kochurova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article shows that intensification of research and educational potential in management of national economy could lead to formation of institutional methods of running market economy. To follow market rules you need proper knowledge. This is the principle role of higher school. It should combine knowledge and experience of the faculty with the creative potential of students. The article underlines the role of state in this process. State must constantly participate in higher school and national economy administration. The author points out to the ruling class destination in national economy and to the fact that it must possess economic knowledge.